2019
DOI: 10.1080/11104929.2019.1688068
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study to investigate the behavior of reinforced concrete slabs with CFRP sheets

Abstract: The current study implements nonlinear finite-element analysis using ANSYS15 software for the preparation of models to investigate the behavior of reinforced concrete slabs strengthened with carbon fiber-reinforced polymer (CFRP) sheets. A comparison between the results of ANSYS, experimental works, and equations of Egyptian Standing Code (ESC) was made for strengthened slabs with different sheet areas. Also, comparisons were carried out between strengthened slabs with equivalent applied areas that differ in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Increasing the flexural load values due to the DTS were compared with the corresponding values when using CFRP for one-way slab models obtained by Omar and Rajai (2020) as well as the results of Rami, Jamal and Hasan (2016). On the other hand, results of the increasing in flexural load capacity of the two-way slab models obtained in the present study were compared with results obtained by Dina (2019), and Balamurugan and Viswanathan (2020), as listed in Table 4.…”
Section: Statistical Comparisonmentioning
confidence: 86%
“…Increasing the flexural load values due to the DTS were compared with the corresponding values when using CFRP for one-way slab models obtained by Omar and Rajai (2020) as well as the results of Rami, Jamal and Hasan (2016). On the other hand, results of the increasing in flexural load capacity of the two-way slab models obtained in the present study were compared with results obtained by Dina (2019), and Balamurugan and Viswanathan (2020), as listed in Table 4.…”
Section: Statistical Comparisonmentioning
confidence: 86%
“…Similarly, (Gherbi et al, 2018) discovered that the flexural failure of an RC two-way slab modeled by Ansys and the failure load is extremely close to the results of the experimental approach. In 2019, (Emarah, 2019) compared the outcomes of ANSYS and Egyptian standing code (ESC) equations in terms of flexural behavior of RC slab strengthened with sheets of carbon fiber-reinforced polymer (CFRP). The results showed that there is a strong agreement between ANSYS and ESC.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the need to strengthen and rehabilitate existing reinforced concrete (RC) structures has increased over the decades. It is often due to the original design limits, construction errors, progressive damages under aggressive environmental conditions [1][2][3]. Therefore, various retrofitting methods have been investigated and developed, e.g., waterproofing, jacking the deteriorated structural members to maintain or even improve their load-carrying capacity, strengthening RC structures using fiber-reinforced polymer (FRP), etc.…”
Section: Introductionmentioning
confidence: 99%